Chapter Monitoring online perception of environmental issues on coasts of Sicily - De Marchi, Damiano (Proceedings e report, 2020)
The analysis of big data on human experience (reviews, comments, ratings, etc.) can provide valuable insights to companies and institutions. This pioneer study applied the artificial intelligence proprietary tools of The Data Appeal Company for a different aim: monitoring the online perception of environmental issues on 88 beaches of Sicily. Results proved that it is possible to monitor environmental situation even to sites where there are no other kind of monitoring, using as bases the free and available contents posted by humans online, processed and analyzed by artificial intelligence